Estrategias para el dimensionamiento y ubicación de generación distribuida (GD) en sistemas eléctricos de distribución. - Barrera Rojas, Ambar Jocabed (2023)
In this paper, the integration of distributed generation (DG) in low voltage networks using radial configuration systems operating in the 220V-127V range of the National Electricity Corporation (CNEL EP Sucumbíos) is carried out in order to evaluate the behavior of electrical variables. To address this issue, a literature review of the deterministic and metaheuristic methods used to determine the dimensioning and location of DG systems was carried out. For the first criterion, photovoltaic panels with specific generation capacities are selected, considering the high availability of solar radiation in the region. For the location, the methodology adopted is based on the implementation of the Particle Swarm Optimization (PSO) algorithm, which seeks to minimize the total losses of the systems. The effectiveness of the method is validated through the comparison with the IEEE 34-node system, obtaining results congruent with those presented by J. Radosavljevic et al. in [68]. Finally, applying PSO allows improving the voltage at the nodes and decreasing the percentage of system losses. However, challenges related to bidirectionality of power flows have been identified, which requires careful attention to ensure system stability.